The Influence of Landscape and Climatic Conditions in the Carpathians on the Formation of Linguistic Personality - Pavliuk, Alisa (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
In the current stage of development of our country globalization and integration processes are becoming more powerful. In these circumstances, the problem of preserving Ukrainian national identity becomes urgent. The article deals with conditions of the linguistic identity as the bearer of the Ukrainian national cultural space. Based on the analysis of current researches of individual language learning the author concludes that linguistic identity is a social phenomenon. The development and establishment of the linguistic personality arises in the process of education, training, communication, i.e. in different activities depending on the nature of the social environment in general and speech environment in particular. However, some scientific research allow to affirm the need to incorporate formative influence of the nature on the linguistic identity. The focus of the article is Carpathian region as an environment in which ethnic culture and language were almost no external influences. An important conclusion from this research is that learning the problem of linguistic identity should take into account forming impact of the environment - both natural and linguistic.